Subdermal solar energy harvesting – A new way to power autonomous electric implants. (1st July 2020) - Tholl, M.V.; Akarçay, H.G.; Tanner, H.; Niederhauser, T.; Zurbuchen, A.; Frenz, M.; Haeberlin, A.
Highlights: Monte-Carlo simulations are used to calculate power of subdermal solar cells. Subcutaneous solar cells may replace batteries in implantable electronic devices. A cardiac pacemaker can be supplied by less than 10 min midday solar irradiation. Simulations revealed that the low wavelength range is strongly absorbed by skin. The subdermal fluence spectrum differs strongly from natural solar irradiance. Solar cell properties must be adapted for spectral subdermal fluence. Abstract: Subdermal solar harvesting has the potential to obviate the need for the periodic battery replacements as required in patients with cardiac pacemakers. The achievable power output of the subdermal solar module depends on implantation depth, optical skin properties and to an important part on solar cell characteristics. Monte Carlo simulations of light distribution in human skin were used to estimate the power output of subdermal solar cells under midday sunlight exposure in geographical mid-latitudes as a function of implantation depth and solar panel size. For the darkest skin type, the daily energy demand of a modern cardiac pacemaker (0.864 J at a power demand of 10 μ W ) can be provided by a 2 cm 2 solar cell implanted subdermally at a depth of 3 mm when exposed to just 11 min of midday, clear sky irradiance. Our study reveals that solar harvesting with relatively small solar cells if optimized for the spectral subdermal fluence has the potential to power cardiac pacemakers in all skin types within reasonable irradiation exposure times. Solar energy harvesting is very promising to power electronic implants.